Prevalence, distribution and amplitude of the complement interference phenomenon in single antigen flow beads assays. (June 2018) - Guidicelli, G.; Visentin, J.; Franchini, N.; Borg, C.; Merville, P.; Couzi, L.; Taupin, J.‐L.
Abstract : HLA antibody detection with single antigen flow beads (SAFB) assays is impaired by complement interference whose frequency, predictability and distribution among HLA antigens have not been analyzed in large cohorts. We compared in two patients' cohorts the routine follow‐up SAFB profiles obtained in class I ( n = 129) and class II ( n = 85) with and without ethylenediaminetetraacetic acid (EDTA)‐treatment. The presence of complement interference was defined according to the reproducibility of the SAFB assays evaluated with our class I and II routine positive control sera. Interference occurred in 29.5% and 45.9% of patients in class I and II, respectively. In the untreated condition, at serum level, neither the number of positive beads, the highest bead mean fluorescence intensity (MFI) nor MFI at bead level, satisfactorily predicted interference. HLA‐C were the least affected among class I beads. HLA‐DQ beads were the most affected in class II. At least one antibody specificity was falsely negative without EDTA for about 3% of sera in class I and 9% in class II. EDTA‐treatment did not significantly modify the low‐MFI strengths (500‐3000 range). This study emphasizes the high frequency of complement interference and the importance and advantages of systematically pretreating sera with EDTA before performing SAFB assays.